2020
DOI: 10.1111/1747-0080.12641
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malnutrition risk and poor food intake in older adults in Indian hospitals: A prospective observational nutritionDay study with novel mapping of malnutrition risk to the Malnutrition Screening Tool

Abstract: Aim Current literature regarding the prevalence and consequences of poor dietary intake and risk of malnutrition in older adults is limited to wealthier regions including the United States, Europe and Australasia. With a rapidly ageing population in India, this prospective observational study aimed to evaluate hospital food intake and malnutrition risk and their impact on hospital length of stay, readmission rates and in‐hospital mortality of older adults in Indian hospitals. Methods Data collected during nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 25 publications
2
6
0
5
Order By: Relevance
“…Daí decorre o fato de que, com o envelhecimento ocorrem limitações siológicas, com alterações no processo mastigatório e digestório, além das DCNT, que de nem o repertório alimentar do idoso. Outras questões também podem ser relacionadas, como a mobilidade, autonomia, condição nanceira e a composição familiar (8)(9)(10)19) .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Daí decorre o fato de que, com o envelhecimento ocorrem limitações siológicas, com alterações no processo mastigatório e digestório, além das DCNT, que de nem o repertório alimentar do idoso. Outras questões também podem ser relacionadas, como a mobilidade, autonomia, condição nanceira e a composição familiar (8)(9)(10)19) .…”
Section: Discussionunclassified
“…Representações negativas sobre a comida de hospital também é encontrada em pesquisas realizadas em outros países (8,9) . Essas questões são amparadas principalmente pelas diferenças no modo de preparo, no sabor, na falta de apetite, no comer sem sentir fome, nas interferências de medicamentos e de patologias, podendo levar a consequências como o prolongamento da hospitalização e a desnutrição (8)(9)(10) . Entende-se que é preciso manter ou resgatar o prazer de comer que deve se estender também ao hospital, possibilitando bem-estar e satisfação aos idosos.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…In combination, responses were mapped to the Malnutrition Screening Tool (MST), a validated predictor of malnutrition risk in hospitalized patients; the MST score could only be determined in N ¼ 14,515 patients, i.e., those who provided answers to these questions. Patients were identified as "at risk of malnutrition" if their responses corresponded to an MST score 2 [31,32]. To report meal intake during the week before hospitalization and on nDay, patients used simple categories (all, about a half, about a quarter, nothing), according to Olin et al [33].…”
Section: Quantifying the Prevalence Of Malnutrition Riskmentioning
confidence: 99%
“…While the study found no statistically significant relationship between mortality, ICU length of stay or rate of mechanical ventilation, the hospital length of stay was significantly 1 week longer in the 36% of patients malnourished upon admission (according to the PG‐SGA after adjusting for APACHE score, age and number of comorbidities). The paper by Wright and colleagues 14 reported a 31% malnutrition risk rate in older (60 years+) patients admitted predominantly for elective reasons to a private hospital in India, however, the proportion at risk increased to 44% during the hospital admission, with over half the at‐risk patients still being provided with a standard diet. Measurement of dietary intake and nutritional status exposes issues in our hospitals and communities and provides opportunities for advocacy in nutrition and dietetics.…”
mentioning
confidence: 99%